Compositional Enhancement of Crustal Magnetization on Mars. Issue 6 (15th March 2021) - AlHantoobi, A.; Buz, J.; O'Rourke, J. G.; Langlais, B.; Edwards, C. S.
Abstract: Martian orbital and lander measurements revealed strong (∼1–2 orders of magnitude greater than Earth) crustal magnetic anomalies and the lack of an active detectable core dynamo. This strong crustal magnetization remains unexplained given that models of an ancient core dynamo on Mars predict surface field strengths comparable to modern Earth. We explored the relationship between Mars' crustal magnetization and its composition in multivariate space. We identified that 530 and 1, 000 nm absorptions (from orbital spectrometers) have unique correlations with crustal magnetization in the Terra Sirenum‐Terra Cimmeria region and ∼13% of the variance of the magnetization can be attributed to these correlations. Because we do not expect the topmost material, detectable by the orbital spectrometers, to retain magnetization from an ancient core dynamo, we propose this material is compositionally similar to the bulk rock below it, which is more likely to retain magnetization. Therefore, the observed variance is a lower limit. Plain Language Summary: Currently Mars has no global magnetic field. However, at some point it did have a global magnetic field. Instruments from past missions have spotted patches on Mars' surface that are strongly magnetized. This can be explained by the fact that the crust was formed during a time when the global magnetic field was present, and so it locked in on that magnetic field. Previous models suggest that when Mars' global magnetic field was present, it was approximately of the same strength as Earth's current field. A magnetic field of this strength would not have produced such a strongly magnetized crust. Therefore, the magnetization strength of those patches is a mystery. We explored the relationships between the strength of the magnetic field on the surface and the composition of the crust. Our findings show that in the area with the strongest magnetic patches, there is a verifiable positive correlation between the magnetic field and mineralogical data. This leads us to believe that the composition of those patches enables them to record the magnetic field exceptionally well. Therefore, Mars' ancient global magnetic field did not need to be anomalously large to produce the strongly magnetized crust we observe. Key Points: The strong magnetization observed in the Terra Sirenum‐Terra Cimmeria region is at least partially due to compositional enhancement The Terra Sirenum‐Terra Cimmeria region has not experienced widespread demagnetization processes since formation The magnetization in the Terra Sirenum‐Terra Cimmeria region is carried in the bulk rock with representative materials exposed at the surface